Comparative treatment outcomes of a single long stent vs. overlapped short stents in acute myocardial infarction - Lee, Doo Hwan; Oh, Seok; Kim, Min Chul; Sim, Doo Sun; Hong, Young Joon; Kim, Ju Han; Ahn, Youngkeun; Han, Jae Bok; Kim, In Soo; Jeong, Myung Ho (Frontiers in Cardiovascular Medicine, 2023)
Objectives: There is no consensus regarding the optimal choice between single long stent (SLS) and overlapped double short stents (DSS) in patients with acute myocardial infarction (AMI). Therefore, we aimed to compare treatment outcomes among patients with AMI treated with these two different stenting methods. Methods: In total, 537 patients with AMI from a single tertiary center were categorized into two groups: (1) those who received an SLS (stent length ≥ 38 mm) (n = 254; 47.3%) and (2) those who received overlapped DSS (individual stent lengths < 38 mm) (n = 283; 52.7%). The primary outcome was the incidence of major adverse cardiac and cerebrovascular events (MACCEs) within 1 year. Results: The mean age of participants was 65.4 years, and 75.0% were male. Patients receiving an SLS had a higher rate of serum creatinine level ≥ 1.5 mg/dL (16.3% versus 8.9%, p = 0.009) but a lower rate of hypertension (46.8% versus 55.8%, p = 0.038), lesser total stent length (38.26 ± 1.31 versus 45.20 ± 9.25 mm, p < 0.001), total procedure time (41.40 ± 15.74 versus 53.31 ± 21.75 min, p < 0.001) and total contrast volume (134.13 ± 30.72 versus 160.57 ± 39.77 mL, p < 0.001) than in those receiving DSS. One-year MACCEs were comparable between the two groups before (hazard ratio [HR], 1.33; 95% confidence interval [CI], 0.80–2.24) and after adjusting for covariates (HR, 1.21; 95% CI, 0.67–2.19). Conclusions: Stenting with an SLS demonstrated similar outcomes compared to those achieved when using stenting with overlapped DSS in patients with AMI. Therefore, if the deliverability is acceptable, stenting with an SLS appears to be a safe and effective strategy for AMI treatment.